(untitled) (CIPEEX, 2022)
COLORECTAL NEOPLASIA IS A DEGENERATION OF THE INTESTINAL EPITHELIUM THAT CAN BE ACCOMPANIED BY POLYPS AND, ACCORDING TO THE NATIONAL CANCER INSTITUTE (2022), COVERS TUMORS THAT START IN THE COLON, RECTUM AND ANUS. IT IS THE THIRD MOST COMMON TYPE OF CANCER IN THE AMERICAS, AFFECTING ALMOST 2 MILLION PEOPLE IN 2018 AND THE SECOND TYPE OF CANCER THAT KILLS THE MOST IN THE AMERICAN CONTINENT, AND THEREFORE IT IS NECESSARY THAT THE POPULATION IS AWARE OF ITS RISK FACTORS, SO THAT THE DIAGNOSIS IS NOT LATE AND THUS INCREASES THE EFFECTIVENESS OF THE TREATMENT. THIS STUDY IS AN INTEGRATIVE LITERATURE REVIEW WHOSE AIM WAS TO SEEK EVIDENCE THAT CORRELATES THE DEVELOPMENT OF CRC WITH GENETICS AND LIFESTYLE. TO CARRY OUT THIS STUDY, A SEARCH WAS CARRIED OUT IN THE ELECTRONIC DATABASES LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS), SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND PUBLISHER MEDLINE (PUBMED).THE DESCRIPTORS USED WERE €ŒCNCER COLORETAL€, €ŒGENTICA€, €ŒDIETA€ AND €ŒOBESIDADE€, WITH THE BOOLEAN AND. THEY WERE INCLUDED ORIGINAL ARTICLES PUBLISHED BETWEEN 2017 AND 2024 WRITTEN IN SPANISH, ENGLISH AND PORTUGUESE. IN THE END, 17 ARTICLES WERE SELECTED, WHICH WERE DIVIDED INTO THREE CATEGORIES OF INFLUENCE: GENETICS, FOOD AND ENVIRONMENT. THE RESULTS POINTED TO A GREAT INFLUENCE OF THE THREE CATEGORIES FOUND. IN THIS WAY, IT WAS PROVED THAT CERTAIN GENES ARE MORE RELATED TO THE DEVELOPMENT OF CCR, SUCH AS THE PROMITOTIC ONES. ON THE OTHER HAND, SOME NULL GENES MAY ALSO FAVOR THIS DISEASE, SUCH AS TUMOR SUPPRESSORS AND DETOXIFICATION GENES, WHICH, WHEN PRESENT, ARE PROTECTIVE. WHEN IT COMES TO FOOD, THE INFLUENCE OF FIBER-RICH FOODS IS NOTED, WHICH HAS SEEN FEWER CASES OF POLYPS AND CRC. OTHER IMPORTANT FINDINGS WERE THE GREATER PREDISPOSITION THAT MEN, PEOPLE OVER 50 YEARS OLD AND OBESE PEOPLE HAVE TO DEVELOP COLORECTAL ADENOMAS.